1989
DOI: 10.1073/pnas.86.21.8467
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency T-DNA-mediated gene tagging in plants.

Abstract: An insertion element [transferred DNA (T-DNA)], transferred by soil agrobacteria into the nuclear genome of plants, was used for induction of gene fusions in Arabidopsis thaliana, Nicotiana tabacum, and Nicotiana plumbaginifolia. A promoterless aph(3')H (aminoglycoside phosphotransferase II) reporter gene was linked to the right end of the T-DNA and transformed into plants along with a plasmid replicon and a selectable hygromycin-resistance gene. Transcriptional and translational reporter gene fusions were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
206
1
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 401 publications
(217 citation statements)
references
References 24 publications
8
206
1
2
Order By: Relevance
“…The high percentage of clones that show morphological symptoms of cytokinin overproduction (21%) indicates that most of the promoter-tagging events led to phenotypic alterations. Koncz et al (1989) who used a similar vector reported that 24% of transformed tobacco clones contained detectable transcriptional reporter gene fusions. However, we cannot exclude that a positive selection for cytokinin-synthesizing clones occurred, nor that some tagging events were not detected because the transcription was too low or expression occurred in cytokinin-insensitive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The high percentage of clones that show morphological symptoms of cytokinin overproduction (21%) indicates that most of the promoter-tagging events led to phenotypic alterations. Koncz et al (1989) who used a similar vector reported that 24% of transformed tobacco clones contained detectable transcriptional reporter gene fusions. However, we cannot exclude that a positive selection for cytokinin-synthesizing clones occurred, nor that some tagging events were not detected because the transcription was too low or expression occurred in cytokinin-insensitive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical mutagenesis studies have greatly improved our understanding of the genetic control of embryo morphogenesis in Arabidopsis (Mayer et al, 1991(Mayer et al, , 1993Meinke, 1986), but T-DNA-mediated gene tagging has the advantage of facilitating gene cloning. Promoter trapping has the further advantage over other mutagenic treatments in that it does not rely necessarily on the identification of mutant phenotypes (which may be low-frequency events) fop successful gene tagging, since the generation of functional gene fusions in situ allows the detection of tagged regulatory elements at high frequency (Koncz et al, 1989;. To date, however, no embryonic genes have been successfully isolated by the use of T-DNA tags (Errampalli et al, 1991;Meinke, 1992;Patton et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The incoming T-DNA may have to interact with this nucleosome structure during the integration process. However, T-DNA may preferentially integrate into transcribed regions of the genome (32,33). These regions are believed to be temporarily free of histones.…”
Section: Discussionmentioning
confidence: 99%